2015
DOI: 10.4103/2008-7802.157543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chewing xylitol containing and herbal chewing gums on salivary mutans streptococcus count among school children

Abstract: Background:The present study aims to assess and compare the reduction in salivary Mutans Streptococci counts after chewing Xylitol, herbal and placebo gums among high school children.Methods:The study was conducted among 72 school children (12–15 years) from 3 randomly selected schools (blocks). Xylitol, herbal and placebo gums were randomly allocated to 3 blocks. Subjects were instructed to chew one pellet four times a day for 21 days. The mean reduction in salivary Streptococcus mutans count was assessed.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…17 Sugar-free gums have been used as a vehicle to administer various substances for therapeutic purposes, including calcium, bicarbonate, carbamide, chlorhexidine, fluorine, xylitol, and the CPP-ACP complex. [3][4][5][6][7] It has been demonstrated that some of these substances have protective properties for the oral cavity, such as xylitol in the control of tooth decay; however, there is concern over the lack of consensus on recommendations for use, which modifies the dosage and perhaps the preventive effect. 18 In this study, the comparison of Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Sugar-free gums have been used as a vehicle to administer various substances for therapeutic purposes, including calcium, bicarbonate, carbamide, chlorhexidine, fluorine, xylitol, and the CPP-ACP complex. [3][4][5][6][7] It has been demonstrated that some of these substances have protective properties for the oral cavity, such as xylitol in the control of tooth decay; however, there is concern over the lack of consensus on recommendations for use, which modifies the dosage and perhaps the preventive effect. 18 In this study, the comparison of Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…counts in both plaque and saliva, suggesting that their regular use (especially those sweetened with xylitol) may reduce the risk of dental caries -even in patients undergoing orthodontic treatment-, common among children, adolescents and young adults. 6 More recently, the CPP-ACP nanocomplex (casein phosphopeptide amorphous calciumphosphate) has been added to chewing gums. Morgan et al in 2008 have found that this component has an anti-cariogenic effect by decreasing bacterial plaque and can help re-mineralize the surface of white spot lesions in radiographic follow-ups.…”
Section: Introductionmentioning
confidence: 99%
“…This Simple single blinded randomized control clinical study included 60 healthy children age between 6-12 years. The involved children were medically free, and don't have orthodontic appliances or periodontal lesions, and have no allergic response to any ingredients of the study products (xylitol -maltitol -mannitolsorbitol -mastic) (2,9,10) . This study was conducted on outpatients who attended the clinics of Pedodontics and Oral Health Department, Faculty of Dental Medicine (Boys, Cairo), Al-Azhar University.…”
Section: Methodsmentioning
confidence: 99%
“…During the study period, the involved children were asked to maintain normal dietary and oral hygiene habits and were instructed to refrain from using commercial chewing gum which is available in the market (9,10) . Each enrolled child in each group was asked to chewing gum for 3 days (3 times per day after meals) using a single gum piece for10 minutes each time.…”
Section: Methodsmentioning
confidence: 99%
“…This randomization procedure was carried out by assistant examiner and were decoded at the end of the study. Baseline unstimulated saliva was collected by instructing the subjects to let saliva collect in oral cavity without swallowing for at least 1 minute and then to expectorate in a sterile dispensing cup for 2 minutes ( 12 ). One pellet of chewing gum was given to subjects in both groups and they were asked to chew under supervision for a period of 15 minutes.…”
Section: Methodsmentioning
confidence: 99%